The Effect of Fermented Moringa oleifera Leaf Meal in The Formulated Diets of Gouramy (Osphronemus gouramy) - Kurniawan, Dhidy; Suharman, Indra; Adelina, Adelina (Fakultas Perikanan dan Kelautan Universitas Riau, 2019)
This research was conducted on Desember 2016 - April 2017. The purpose of this study is to determine the amount of fermented flour from Moringa leaf in the feed which affect the growth, feed efficiency, feed digestibility and protein retention in gouramy (Osphronemus gouramy). This study uses a completely randomized design (CRD) with one factor, 5 treatments and 3 replications. The treatment with substitution of fermented moringa leaf flour, Controls (0: 100%), P1 (10: 90%), P2 (15: 85%), P3 (20: 80%), P4 (25: 75%). The feed contain protein of 30%. The results showed that the best result is the highest treatment from P2 (15: 85%) with a specific growth rate of 1.58% / day, feed efficiency rate of 18.44%, 73.82% of feed digestibility and protein retention 15.82%.